Rivers and the Redefinition of Time in Ovid’s Poetry - Batty, Rebecca (2021)
This thesis explores how experiences with rivers colour the perception of time and memory in Ovid’s works. Explorations of attitudes towards the environment are becoming more popular, particularly with contemporary concerns about environmental damage, as we re-evaluate our perception of ourselves and the environment. However, as part of this re-evaluation, the perception of time as a significant factor within experience of the natural environment is rarely considered. Through their use as a metaphor for time, rivers are the ideal focus point for considering how Ovid’s experiences with the natural environment affect the depiction of time and continuity across his extant corpus. This thesis draws together studies of the ancient environment, literary analysis, and spatial studies to enable a holistic analysis of rivers in Ovid’s poetry, showing how river behaviour affects the depiction of poetic continuity, in connection with natural (deep) time. As Ovid’s poetry plays most explicitly with the strong metaphorical tradition of the river of time developed in poetry, this thesis especially explores how the perception of time and the environment is used to help navigate concerns about poetic memory, the poetic canon, and the poet’s place both within and without the environment of Rome. Through analysis of both natural and unnatural river behaviour in Ovid’s works, this thesis argues that the poet aligns his works with the continuity of natural time, represented by the river. Key aspects of this continuity are movement and transformation, in contrast to continuity which stays static. This thesis argues that Ovid’s particular form of continuity, tied to disruptive river behaviour, interacts with temporal manipulation in Augustan political narratives – particularly responding to and mirroring Augustan narratives of continuity. Analysing across Ovid’s corpus, this thesis also argues that the natural environment is not only subject to but also directly affects the perception of time, evident in particular when immobile rivers in Ovid’s exile poetry highlight an initial loss of time, and threatened continuity. The threatened continuity of the natural environment is caused by external, overwhelming forces, demonstrating that in Ovid’s works, continuity in the natural environment was not always guaranteed – a point resonant for our current environmental crisis.